2014
DOI: 10.4161/15384101.2014.968426
|View full text |Cite
|
Sign up to set email alerts
|

Targeting chemokine pathways in esophageal adenocarcinoma

Abstract: y These authors Contributed equally to this work. E sophageal adenocarcinoma (EAC) is one of the fastest growing malignancies in the US and needs newer therapeutic and diagnostic strategies. Chronic inflammation plays a role in the pathogenesis of EAC and contributes to the dysplastic conversion of normal esophageal epithelium to Barrett's esophagus and frank adenocarcinoma. Chemokines play important roles in mediating inflammation and recent evidence implicates these ligands and their receptors in the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 115 publications
(104 reference statements)
2
35
0
Order By: Relevance
“…The overall and disease-free Fig. 1 The structure of chemokines and their receptors [21][22][23][24][25] survival rates were significantly lower in patients with positive CXCL12 expression compared to those with negative CXCL12 immunoreactivity, what was confirmed using univariate analysis. The authors concluded that CXCL12 expression is an important predictor of lymph node metastasis and poor prognosis of ESCC patients' survival [44].…”
Section: Chemokines and Their Receptors-the Role In Esophageal Cancersupporting
confidence: 69%
See 4 more Smart Citations
“…The overall and disease-free Fig. 1 The structure of chemokines and their receptors [21][22][23][24][25] survival rates were significantly lower in patients with positive CXCL12 expression compared to those with negative CXCL12 immunoreactivity, what was confirmed using univariate analysis. The authors concluded that CXCL12 expression is an important predictor of lymph node metastasis and poor prognosis of ESCC patients' survival [44].…”
Section: Chemokines and Their Receptors-the Role In Esophageal Cancersupporting
confidence: 69%
“…On the other hand, a developing neoplasm might induce both local and systemic inflammatory responses [28]. It has been shown that various proinflammatory mediators, including cytokines, reactive oxygen mediates, increased expression of oncogenes, matrix Table 1 The classification of chemokines and their receptors [21][22][23][24] Subfamily of chemokines Name of chemokines Other names of chemokines Receptors…”
Section: Chemokines and Their Receptors-the Role In Cancer Developmentmentioning
confidence: 99%
See 3 more Smart Citations